Ochratoxin A in raisins samples marketed in São Paulo, Brazil - Almeida, Adriana Palma de (2006)
The present study aimed to evaluate a methodology for analyzing ochratoxin A (OTA) in raisins samples marketed in São Paulo, Brazil. OTA was extracted with methanol:water (80:20, v/v) and diluted with phosphate buffer solution, and purified through an immunoaffinity column. OTA was separated and quantified using HPLC with fluorescence detection. The established detection and quantification limits were 0.24 and 0.80 ng/g, respectively. The recoveries values were 81.6, 80.4 and 81.9%, and the relative standard deviations (RSD) were 6.0, 4.3, and 6.1 % at 2.0, 5.0 and 10.0 ng/g levels, respectively. Of twenty black raisin samples analyzed 10 (50 %) contained OTA at levels ranging from 1.3 to 39.1 ng/g. All of twenty-two white raisin samples showed no contamination with OTA.